The Eccentrics of Istanbul: Chan, Art, and Cross-Asian Networks in the Ming. (3rd July 2018) - Paul, Paramita
Abstract : Images of Chan eccentrics were a popular artistic theme in East Asia from the eleventh century onwards. In the Ming dynasty (1368–1644), the theme was carried across the Eurasian continent to Persia. This article examines two fifteenth-century paintings of Chan eccentrics in Persian albums, currently in the Topkapi Palace Museum in Istanbul. It argues that the paintings are different both thematically and visually, and it explores them in the contexts of their specific albums and histories of collection and viewing. The article shows that each painting brings together visual and conceptual elements of many traditions, including Chinese, Persian and Eurasian traditions and Islamic mysticism. The paintings question common modes of art historical categorization. At the same time, they are evidence of lively artistic networks between Ming China and the Eurasian continent.